Improving The Efficiency Of Sip Authentication Based On The Pre-Calculated Look-Up Table - Jaber, Aws Naser (2013)
IP phones have benefited greatly from the ever-increasing capabilities of computer hardware in general, including faster microprocessors, larger memory capacity, and greater network bandwidth. A single IP phone shipping in 2010 has far more computing capacity than most of the early PBXs. This trend will only continue. IP phones are adding color displays with full-blown Web browsers. Some are adding embedded Warning Do not forget to investigate how data is stored on a local system or any intermediary system. If, for instance, all log files of IM chat sessions are stored in clear, unencrypted text on a local computer where multiple people have access to the computer, the fact that the IM client encrypts sessions between the computers and the server does not fully protect those sessions. The session transcripts could still be read locally by anyone with access to the local computer. Today, while many companies might still choose to buy from a single vendor for the sake of convenience, the reality is that in the era of interoperable protocol standards like Session Initiation Protocol (SIP), the companies are no longer required to buy from the same vendor. The session initiation protocol (SIP) has recently become the main signaling protocol for Internet applications. The wide range of SIP services raises many concerns on SIP security. Thus, the most popular SIP authentication schemes were studied in this paper. The previous cryptographic scheme known as Yoon’s scheme proposes SIP authentication that brings efficiency in security but is costly in terms of time.